Life Out of the Shadows : Impacts of Amnesties in the Lives of Refugees - Ibáñez, Ana María; Moya, Andres; Ortega, María Adelaida; Rozo, Sandra V.; Urbina, Maria Jose (World Bank, Washington, DC, 2022)
This paper examines the effects of a government regularization program offered to half a million Venezuelan refugees in Colombia. For this purpose, 2,232 surveys of refugee families were collected and used to compare refugees who arrived in Colombia around a specified eligibility date in 2018. The analysis finds that program beneficiaries experienced improvements in consumption (60 percent), income (31 percent), physical and mental health (1.8 sd), registration rates in the system that assesses vulnerability and awards public transfers (40 pp), and financial services (64.3 pp), relative to other refugees. The program also induced a change in labor formalization of 10 pp.